2019
DOI: 10.1177/0300060519877321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dasatinib on CD8+T, Th1, and Treg cells in patients with chronic myeloid leukemia

Abstract: To investigate the immunomodulatory effects of the tyrosine kinase inhibitor (TKI) dasatinib on T-cell subtypes in patients with chronic myeloid leukemia (CML). Methods: T helper (Th) 1, Th2, regulatory T (Treg), and CD8 þ T cell levels were detected in patients with CML (n ¼ 9) before and after dasatinib treatment. The corresponding response level at the time of a blood test was evaluated. Results: After dasatinib treatment, six patients achieved a better response level, while three did not show improved resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 24 publications
(31 reference statements)
2
8
0
3
Order By: Relevance
“…Aside from early work revealing the generation of LGL in dasatinib-treated patients 15,16 , very few studies have studied dasatinib action on CD8 T-cells. However, the study by Kreutzman et al, which showed that dasatinib treatment increased the numbers of granzyme B expressing memory CD4 and CD8 T-cells 12 , and the recent study by Wei et al showing an increase of CD8 T-cells concomitantly with decreased Treg 11 , are in accordance with our own results showing an increased CD49d expression level on innate CD8 T-cells. Indeed, we have previously shown that innate CD8 T-cells have a higher cytotoxic potential than conventional CD8 T-cells 27,28 and that the IFNγ secretion function is correlated with the expression of CD49d 26 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Aside from early work revealing the generation of LGL in dasatinib-treated patients 15,16 , very few studies have studied dasatinib action on CD8 T-cells. However, the study by Kreutzman et al, which showed that dasatinib treatment increased the numbers of granzyme B expressing memory CD4 and CD8 T-cells 12 , and the recent study by Wei et al showing an increase of CD8 T-cells concomitantly with decreased Treg 11 , are in accordance with our own results showing an increased CD49d expression level on innate CD8 T-cells. Indeed, we have previously shown that innate CD8 T-cells have a higher cytotoxic potential than conventional CD8 T-cells 27,28 and that the IFNγ secretion function is correlated with the expression of CD49d 26 .…”
Section: Discussionsupporting
confidence: 92%
“…For example, in melanoma, sarcoma, colon and breast cancer-bearing mice, dasatinib increases CD8 T-cells concomitantly with decrease in regulatory CD4 T-cells 10 . Recently, the same effect was observed in some patients with chronic myeloid leukemia (CML) 11 . In clinical use, immunostimulatory effects have been observed during long-term use of dasatinib [12][13][14][15] .…”
supporting
confidence: 57%
“…While dasatinib is recognized as the suitable candidate due to its targeting multiple kinases involved in immune-oncogenic pathways, it shows promise in modulating the tumor immune microenvironment as well. Dasatinib treatment increased Th1 and CD8+T cell levels in patients with chronic myeloid leukemia who had better therapeutic responses [ 37 ]. Currently, dasatinib is being investigated for isocitrate dehydrogenase (IDH)-mutant advanced intrahepatic cholangiocarcinoma (NCT02428855).…”
Section: Discussionmentioning
confidence: 99%
“…Ishiyama et al recently reported that CD56 − NK cells with PD-1 expression were induced by chronic activation through CMV reactivation in CML or Ph + ALL patients during dasatinib therapy [ 43 ]. Interestingly, the expansion of CD56 − NK cells was associated with a higher rate of DMR, and Wei et al also reported that dasatinib increased the percentage of Th1 and CD8 T cells and decreased Treg cell levels in the peripheral blood of CML patients who responded to therapy [ 44 ]. Overall, dasatinib seems to have the potential to enhance both innate and adaptive immunity to eradicate CML-LSCs in some patients.…”
Section: Immune Status Of CML Patientsmentioning
confidence: 99%